Advanced functional materials based on nanocellulose/Mxene: A review - Al-Fakih, Ghassan O.A.; R., A. Ilyas; A., Atiqah; M.S.N., Atikah; Saidur, R.; Dufresne, Alain; Saharudin, Mohd Shahneel; Abral, Hairul; S., M.Sapuan (Elsevier, 2024)
The escalating need for a sustainable future has driven the advancement of renewable functional materials. Nanocellulose, derived from the abundant natural biopolymer cellulose, demonstrates noteworthy characteristics, including high surface area, crystallinity, mechanical strength, and modifiable chemistry. When combined with two-dimensional (2D) graphitic materials, nanocellulose can generate sophisticated hybrid materials with diverse applications as building blocks, carriers, scaffolds, and reinforcing constituents. This review highlights the progress of research on advanced functional materials based on the integration of nanocellulose, a versatile biopolymer with tailorable properties, and MXenes, a new class of 2D transition metal carbides/nitrides known for their excellent conductivity, mechanical strength, and large surface area. By addressing the challenges and envisioning future prospects, this review underscores the burgeoning opportunities inherent in MXene/nanocellulose composites, heralding a sustainable frontier in the field of materials science.